2017
DOI: 10.1038/srep45232
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects on gut microbiota regulate hepatic carcinogenic outcomes

Abstract: Emerging evidence points to a strong association between sex and gut microbiota, bile acids (BAs), and gastrointestinal cancers. Here, we investigated the mechanistic link between microbiota and hepatocellular carcinogenesis using a streptozotocin-high fat diet (STZ-HFD) induced nonalcoholic steatohepatitis-hepatocellular carcinoma (NASH-HCC) murine model and compared results for both sexes. STZ-HFD feeding induced a much higher incidence of HCC in male mice with substantially increased intrahepatic retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 45 publications
3
62
0
Order By: Relevance
“…Recent studies demonstrated the relationship between microbiota and hepatocellular carcinogenesis [38]. The results established that sex-based disparity in liver carcinogenesis is connected with the gut microbiota and tumour-suppressive miRNAs, miRNA-22, miRNA-26a, miRNA-26a-1, miRNA-192, miRNA-122 and miRNA-125b.…”
Section: Microbiota and Hepatic Carcinomamentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies demonstrated the relationship between microbiota and hepatocellular carcinogenesis [38]. The results established that sex-based disparity in liver carcinogenesis is connected with the gut microbiota and tumour-suppressive miRNAs, miRNA-22, miRNA-26a, miRNA-26a-1, miRNA-192, miRNA-122 and miRNA-125b.…”
Section: Microbiota and Hepatic Carcinomamentioning
confidence: 88%
“…Nevertheless, the controlling mechanism is uncertain. Increased concentrations of farnesoid X receptor (FXR), a bile acid nuclear receptor, in female animals may augment the expression of miRNA-26a, miRNA-26a-1 and miRNA-122 as the suppressors in HCC, probably causing a reduction of the risk of HCC in female mice [38]. Moreover, butyrate from microbiota increases programmed cell death via up-regulation of miRNA-22 expression and reduction of sirtuin1 expression in hepatic cells [39].…”
Section: Microbiota and Hepatic Carcinomamentioning
confidence: 99%
“…Multifaceted approaches that integrate metagenomic and metabolomic profiling from well-characterized gnotobiotic animal models will be essential in determining the role of microbiota-mediated alterations in bile acids in the development of gastrointestinal cancers. In addition, distinct profiles of gut microbiota and bile acids have been reported in males and females, and these might contribute to the sex-based disparity in liver carcinogenesis 202 . A better understanding of the hormonal actions of bile acids on their receptors will reveal opportunities for prevention and control of gastrointestinal cancers that often exhibit gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a higher abundance of Corynebacterium, Corynebacteriaceae, Rhodococcus, Nocardiaceae, Adlercreutzia, Bacillus, Bacillaceae, Staphylococcus, Desulfovibrio and Desulvibrionales, and Clostrodium were found in male mice in comparison to female mice. (81) This may result in altered microbial bile acid metabolism and a substantial increase of intrahepatic retention of hydrophobic bile acids in male mice more with decreased hepatic expression of tumor suppressive microRNAs.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%